1988
DOI: 10.1159/000132500
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of structural aberrations in human sperm chromosomes

Abstract: We have analyzed structural aberrations in 5,000 sperm chromosome complements obtained from 20 men over a 5-yr period by fusion of human sperm with hamster eggs. Detailed data are presented on 366 abnormal cells with 379 analyzable breakpoints. The frequency of cells with structural aberrations ranged from 1.9% to 14.5% among donors; this interindividual variability was statistically significant (p < 0.0001). In contrast, repeat samples from individual men showed no significant variation over time. The number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
2

Year Published

1990
1990
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 12 publications
3
41
2
Order By: Relevance
“…In both younger and older patients, chromosomes 19 and 20 had an excess of abnormalities, whereas chromosomes 3 and 6 had less than expected. Non-random distribution of breaks on chromosome 9 has been reported in sperm karyotypes 14 and in FISH studies an age dependent linear trend on chromosome 9 breaks was reported. 22.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In both younger and older patients, chromosomes 19 and 20 had an excess of abnormalities, whereas chromosomes 3 and 6 had less than expected. Non-random distribution of breaks on chromosome 9 has been reported in sperm karyotypes 14 and in FISH studies an age dependent linear trend on chromosome 9 breaks was reported. 22.…”
Section: Discussionmentioning
confidence: 84%
“…In sperm karyotypes, obtained after in vitro penetration of hamster oocytes, structural chromosome abnormalities have been observed far more frequently than numerical aberrations. [13][14][15] In a review, Templado et al 16 reported a median percentage of 6.6% of structural aberrations and 1.8% of numerical abnormalities. Several authors have explored the relationship between age of the donor and sperm structural aberrations (reviewed by Buwe et al 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…abnormality Less Upper P-value Age and chromosome abnormalities in human sperm M Bosch et al distribution of breaks in this chromosome was previously reported in sperm karyotypes of normal men. 4,20 These studies are coincident in that chromosome 9 has a higher number of breakpoints than expected by chance and also in that 50% of the breakpoints are located between the centromere and the 9qh þ segment. In somatic cells, Starke et al 22 proposed that the homology between 9p12 and 9q13 -q21.1 with the short arms of the acrocentric human chromosomes, made these chromosomes more prone to chromosome rearrangements and increased the risk of an interchromosomal effect among them.…”
Section: Discussionmentioning
confidence: 86%
“…Chromosome 9 was chosen because of its high incidence of breaks shown in somatic cells and spermatozoa. 20,21 We also investigated whether chromosome 9 structural or numerical abnormalities influenced by donor age were more likely to occur in X-or Y-bearing sperm. We found increased frequencies of all types of structural chromosome 9 aberrations analysed (deletions and duplications of the 9cen and 9q regions) with regard to age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation